Izbrana vprašanja povezovanja sistemov socialne varnosti v luči zaposlovanja delavcev iz držav EU in tretjih držav - Rataj, Primož (Delavci in delodajalci, 2022)
The contribution is focused on selected issues of coordination of social security systems that are presently important in the context of cross-border employment cases in Slovenia. Due to the frequency and number of A1 forms in Slovenia and the statistical changes in the previous years, the contribution attempts to seek delimitation between posted workers and the pursuit of work activities in several Member States. Moreover, some contentious issues are exposed, namely contribution basis in the case of posted workers and the theoretical grounds for the initiatives of sending and receiving Member States in the framework of competence to withdraw or rescind A1 form. In a broader context, the contribution addresses the intertwined area of applicable legislation rules in the fields of labour and social security law, while different legal grounds for social security coordination are concisely outlined.
Keywords: activities in several Member States; applicable legislation; contribution basis; coordination of social security systems; delimitation; delovno pravo; napoteni delavci; posted workers; Slovenija; socialna varnost; socialni prispevki; tuji delavci